Awareness of Breastfeeding Laws and Provisions of Students and Employees of Institutions of Higher Learning in Georgia. (May 2019) - Anderson, Alex Kojo; Johnson, Evan; Motoyasu, Nicole; Bignell, Whitney E.
Background: Over the past 2 decades, southern states in the United States have recorded the lowest breastfeeding rates. It is not known whether awareness of breastfeeding laws and provision of resources play any role in their breastfeeding practices. Research aims: The aims were (a) to describe awareness of breastfeeding laws and provisions by students and employees of institutions of higher learning in the state of Georgia, (b) to describe awareness by race and ethnicity, and (c) to determine factors associated with awareness of breastfeeding laws and provisions among students and employees within Georgia institutions of higher learning. Methods: A cross-sectional online survey of students ( n = 1, 923) and employees ( n = 1, 311) associated with five institutions within the University System of Georgia ( N = 3, 271) was completed. Convenience sampling was used. Data were collected through Qualtrics. Chi-square test was used to examine differences between groups, while logistic regression was used to examine associations. Results: Participants included 33.3% undergraduate, 26.2% graduate students, 24.6% staff, 14.2% faculty, and 1.7% administrators. Over two thirds were female and white. Almost one third reported having a child or children. Awareness of breastfeeding laws and provisions was very low among respondents, with 26.6 and 9.6% aware of federal and state provisions, respectively. While less than 10% were familiar with the Baby Friendly Hospital Initiative program, 52.6% reported their institution provides a supportive environment for breastfeeding. Being a student and being a minority were negatively associated with awareness of laws and provisions that support breastfeeding. Conclusion: The need for focused efforts on increasing awareness of legislative and institutional provisions and support for breastfeeding exists.